Cover Picture: A Straightforward Approach to Tetrahydroindolo[3, 2‐b]carbazoles and 1‐Indolyltetrahydrocarbazoles through [3+3] Cyclodimerization of Indole‐Derived Cyclopropanes (Chem. Eur. J. 4/2016). Issue 4 (16th December 2015) - Ivanova, Olga A.; Budynina, Ekaterina M.; Khrustalev, Victor N.; Skvortsov, Dmitriy A.; Trushkov, Igor V.; Melnikov, Mikhail Ya.
Abstract : Dimerization is among the most challenging and fascinating reactions that, within one step, can provide a significant increase in structural complexity in a highly stereoselective manner. Indole‐containing donor‐acceptor cyclopropanes are appropriate candidates for dimerization reactions that provide rapid accesses to various biologically active bis‐indole compounds. More information can be found in the Communication by E. M. Budynina, et al. onpage 1223 ff.